The protective rules regulating commercial advertising - MAAKOUF, Asma (Journal of Human Sciences, 2020)
Commercial advertising is considered the most important means of marketing products and services, it is also regarded as a manifestation of legitimate competition, as it represents a link between the consumer and the advertiser, who is committed to providing the consumer with the necessary information about the product or service. And in order to achieve the prevention protection of the consumer against the misleading advertisements, there must be a self-regulation for commercial advertising.Therefore, the publicity message must respect the legal rules, in addition to complying with the general principles stipulated, and respecting the public order and the moral values. However, all this is not enough to reduce the risks of the false advertisements in which the rules and regulations established by the law are not respected.In this regard, it is best for the legislator to issue a special law that regulates advertisements and establishes controls, but in return does not exaggerate establishing controls that would paralyze the movements of advertising activity.